Absorptive Capacity (AC) : Knowledge Generation and its Evolution From Variable to Construct (2017)
ABSTRACT: The article purpose is to analyze knowledge generation based on the Adsorptive Capacity of firms (AC). This study was done considering the currently existing literature between 2005 and 2014 in recognized journals of technology and innovation as per the Journal Citations Report (JCR) Scimago Journal & Country Rank (SJR). The results show the predominance of studies with quantitative, multidimensional, and interdisciplinary approaches, which look to enhance the analysis levels over theoretical perspectives, the determinants and CA factors, realize construct update and validation with first and second order data, as well as develop and apply measurement scales CA.